ANALISA TROUBLE SHOOTING AIR CONDITIONER NIPPON DENSO PADA UNIT SCANIA P380 MENGGUNAKAN MICROCONTROLER - Danang Danang; Mat Toyib (Jurnal Publikasi Teknik Informatika, 2022)
Consumables inventory information system is used to control and supervise the management of consumables in carrying out the management of consumables, they often face problems. These problems such as inaccurate counting of goods, recording process, transaction data documentation is hampered, and inventory control is not optimal. The thing that is done to minimize these problems is the construction of an information system for managing consumables inventory. This system was created by developing an existing system. The purpose of developing this system is to provide convenience for users to obtain the required information quickly and accurately. The stages of system development used in the development of this system are system analysis, system design and system implementation. The auxiliary software used to implement the system design is Delphi Borland The consumables inventory information system is built based on user needs so that requirements specifications are generated. The database in this system includes a table of goods, users, suppliers, circulation, invoices, inventories, proposals for goods and expiration of goods.